Efektivitas Permainan Bendera Buah terhadap Perkembangan Motorik Kasar Anak Usia 5-6 Tahun - Rahmatullah, Sakdiah; Ismet, Syahrul (Asian Journal of Early Childhood and Elementary Education, 2023)
This research is motivated by the media and game tools used by the teacher in activities to develop children's gross motor skills which are less effective and varied, such as using basketball and small balls so the purpose of this study is to determine the effectiveness of playing fruit flags on the gross motoric development of children aged 5-6 years in Taman Kanak-Kanak Negeri Pembina Talamau District, at West Pasaman. This study used a quantitative approach in the form of a quasi-experimental with a nonequivalent control group design. The population of this study were children in Taman Kanak-Kanak Negeri Pembina, Talamau District, at West Pasaman, totaling 88 children divided into 6 study groups. The sampling technique used purposive sampling technique, namely groups B1 and B2 each consisting of 12 children. Data collection techniques with action tests using 4 statement items. Data analysis techniques used the normality test, homogeneity test and hypothesis testing and effectiveness test with the help of SPSS version 26 for windows. The results showed that the data were normally distributed and homogeneous. Furthermore, based on the t test it is known that (2-tailed) is 0.02 <0.05 and the effect size test has a value of 1.025 so it can be concluded that there is effectiveness of playing fruit flags on gross motoric development of children aged 5-6 years in Taman Kanak-Kanak Negeri Pembina, Talamau District, West Pasaman.